2020
DOI: 10.1002/dc.24589
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of cervical lymph nodes: Comparison of liquid based cytology (SurePath) and conventional preparation

Abstract: Background Fine needle aspiration cytology (FNAC) is the first diagnostic step in patient with cervical lymphadenopathy because of its simplicity, safety and early availability of the results. Liquid‐based cytology (LBC) is an alternative processing method which is used for both gynecological and nongynecological samples. Literature reviewed show few studies comparing LBC with conventional preparation (CP). Aim The present study was undertaken to evaluate the efficacy of LBC and comparison of LBC and CP in cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Rapid and proper fixation is a specific advantage of LBC that provides cytopathologists with fewer air‐drying artifacts, as well as well‐preserved nuclear and cytoplasmic details 11,12 . Due to these advantages, the ND cases in our study comprised 3.0% in the LBC group, which is approximately four times less than in the CG.…”
Section: Discussionmentioning
confidence: 87%
“…Rapid and proper fixation is a specific advantage of LBC that provides cytopathologists with fewer air‐drying artifacts, as well as well‐preserved nuclear and cytoplasmic details 11,12 . Due to these advantages, the ND cases in our study comprised 3.0% in the LBC group, which is approximately four times less than in the CG.…”
Section: Discussionmentioning
confidence: 87%
“…Based on their observations, the authors concluded that LBC was advantageous in comparison to conventional cytology in the diagnosis of metastatic squamous cell carcinoma. The material was developed and stained by the PAP method with a BD PrepStain slide processor (SP) [3]. In diagnosing cervical lymphadenopathy, Bandoh et al found LBC from FNA material from lymph nodes to be useful in the identification of metastases -largely through greater diagnostic accuracy by reduction of nondiagnostic preparations.…”
Section: Lymph Nodesmentioning
confidence: 99%
“…The liquid-based cytology method makes it possible to obtain a cleaner background, increased cellularity and well-preserved nuclear details through technically improved sample preparation for diagnosis. However, the method remains a diagnostic challenge as the sample processing technique and preservative fluid may change cell morphology and introduce artifacts [3].…”
Section: Introductionmentioning
confidence: 99%